2008
DOI: 10.1002/dev.20279
|View full text |Cite
|
Sign up to set email alerts
|

Marked for life? Effects of early cage‐cleaning frequency, delivery batch, and identification tail‐marking on rat anxiety profiles

Abstract: Daily handling of preweanling rats reduces their adult anxiety. Even routine cage-cleaning, involving handling, reduces adult anxiety compared with controls. Cage-cleaning regimes differ between animal breeders, potentially affecting rodent anxiety and experimental results. Here, 92 adult male rats given different cage-cleaning rates as pups, were compared on plus-maze, hyponeophagia, corticosterone, and handling tests. They were pair-housed and half were tailmarked for identification. Anxiety/stress profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 66 publications
1
27
1
Order By: Relevance
“…Furthermore, in a follow-up study, we found no significant effects on pup handleability or anxiety profiles in adulthood (Burn et al, 2008). However, we found that cannibalism increased with more frequent cage-cleaning, which is consistent with the small-scale study by Cisar and Jayson (1967), and with common perception (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, in a follow-up study, we found no significant effects on pup handleability or anxiety profiles in adulthood (Burn et al, 2008). However, we found that cannibalism increased with more frequent cage-cleaning, which is consistent with the small-scale study by Cisar and Jayson (1967), and with common perception (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Here and in a follow-up study (Burn et al, 2008), we found no clear benefits of frequent cagecleaning to breeding rats, but it did increase the likelihood of cannibalism, and the cleaning process itself might have triggered parturition. We would therefore recommend that cages are not cleaned during the last few days of pregnancy (possibly avoiding premature induction of birth) or the first 2 days following birth (avoiding acute early disturbances).…”
Section: Resultscontrasting
confidence: 53%
“…In addition to genetic differences between outbred SD or Wistar rats from different vendors or locations of the same vendor, intrastrain differences can also be due to housing and handling conditions at the vendor during development of the animals [13,15,[36][37][38]. In the present and previous studies in SE models by our group, all rats were kept under the same controlled environmental conditions once they arrived in our laboratory.…”
Section: Discussionmentioning
confidence: 93%
“…Handling is stressful for many animals, which can affect both animal welfare and the scientific data. 16 Observing animals following handling (for example, to record body weight) can facilitate observing some relevant behaviours, such as the postsurgical behaviours outlined in section 2.5.2, and reduce the time needed for the assessment.…”
Section: Handling the Animalsmentioning
confidence: 99%